Characterisation of phenolic compounds, including flavonoids and tannins, of ten Ethiopian browse species by high performance liquid chromatography - Mueller-Harvey, I.; Reed, J.D.; Hartley, R.D. (Wiley, 1987)
Examines aqueous acetone extracts of leaves from ten browse plants by high performance liquid chromatography and thir layer chromatography for their phenolic constituents.